Dysfunction of human Rad18 results in defective postreplication repair and hypersensitivity to multiple mutagens - Tateishi, Satoshi (The National Academy of Sciences, 2000)
Postreplication repair functions in gap-filling of a daughter strand on replication of damaged DNA. The yeast Saccharomyces cerevisiae Rad18 protein plays a pivotal role in the process together with the Rad6 protein. Here, we have cloned a human homologue of RAD18, hRAD18. It maps on chromosome 3p24–25, where deletions are often found in lung, breast, ovary, and testis cancers. In vivo, hRad18 protein binds to hHR6 protein through a conserved ring-finger motif. Stable transformants with hRad18 mutated in this motif become sensitive to UV, methyl methanesulfonate, and mitomycin C, and are defective in the replication of UV-damaged DNA. Thus, hRAD18 is a functional homologue of RAD18.